2016
DOI: 10.1371/journal.pone.0149723
|View full text |Cite|
|
Sign up to set email alerts
|

Engineering Multi-Walled Carbon Nanotube Therapeutic Bionanofluids to Selectively Target Papillary Thyroid Cancer Cells

Abstract: BackgroundThe incidence of papillary thyroid carcinoma (PTC) has risen steadily over the past few decades as well as the recurrence rates. It has been proposed that targeted ablative physical therapy could be a therapeutic modality in thyroid cancer. Targeted bio-affinity functionalized multi-walled carbon nanotubes (BioNanofluid) act locally, to efficiently convert external light energy to heat thereby specifically killing cancer cells. This may represent a promising new cancer therapeutic modality, advancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Presently, a high level of biological and chemical functionalization potential is available for binding of targeting ligands to MWCNT nanoparticles, thus mediating cancer cell recognition and subsequent nearfield cell ablation. Expanding on our previous study 20 of MWCNT nanoparticle-mediated targeting strategy, here we specifically target prostate-specific membrane antigen (PSMA) expressed in CaP cells by optimizing the nanoparticle functionalization and antibody conjugation chemistry. We also aimed to show that highly efficient targeting should place a sufficient number of nanoparticles directly on the surface of cells so as to deliver exquisite extreme nearfield heat energy sufficient for cell ablation without bulk heating.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, a high level of biological and chemical functionalization potential is available for binding of targeting ligands to MWCNT nanoparticles, thus mediating cancer cell recognition and subsequent nearfield cell ablation. Expanding on our previous study 20 of MWCNT nanoparticle-mediated targeting strategy, here we specifically target prostate-specific membrane antigen (PSMA) expressed in CaP cells by optimizing the nanoparticle functionalization and antibody conjugation chemistry. We also aimed to show that highly efficient targeting should place a sufficient number of nanoparticles directly on the surface of cells so as to deliver exquisite extreme nearfield heat energy sufficient for cell ablation without bulk heating.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that, with increasing the concentrations of ZnO NPs in 48 and 72 hours of treatment, the survival rate of MCF-7 cell lines in breast cancer decreased. Dotan et al 44 developed a nanofluid platform by conjugating multi-walled carbon nanotubes (CNTs) with either thyroid-specific antibody or thyroid-stimulating hormone. The nanofluid selectively targeted and killed the papillary thyroid cancer cells in vitro with minimal cytotoxic effect on the non-targeted cells.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…A different novel strategy to control thyroid cancer includes targeting the TSHR with nano-liposomes coated with fragments of TSH and loaded with chemotherapeutic agents [24]. Another proposed approach is based on using TSHR binding carbon-walled nanotubes, which have the ability to convert external light energy to heat energy resulting in killing the cancer cells locally [25]. Also, small molecule antagonist to the TSHR would offer yet another approach to inhibit thyroid cancer progression by suppressing TSHR signalling [26].…”
Section: In Vivo Practical Applications Of Tshr Researchmentioning
confidence: 99%